Pengaruh Lingkungan Kerja, Komunikasi, Disiplin Dan Kepuasan Kerja Terhadap Kinerja Pegawai Negeri Sipil Dan Honorer Dinas Perpustakaan Dan Kearsipan Kabupaten Labuhanbatu (Studi Kasus Perpustakaan Umum Labuhanbatu) - Aisah, Siti (Universitas Labuhanbatu, 2021)
This study aims to determine the influence of work environment, communication, discipline, and job satisfaction on employee performance. The type of research used is quantitative research. The research was conducted in Labuhanbatu Public Library. The number of respondents was 53 people. This study divides the questionnaire to employees and division heads. Data processing and analysis techniques using SPSS version 23. The results stated that the work environment, communication, work discipline and work environment have a significant effect individually and have a significant effect together on the performance of employees in the Labuhanbatu Public Library. A comfortable working environment and a high level of communication, discipline will improve employee performance.